STRATEGI KOMUNIKASI HUMAS PT KERETA API INDONESIA (PERSERO) DAERAH OPERASI 1 JAKARTA DALAM PENERTIBAN LAHAN PROYEK TRANSIT ORIENTED DEVELOPMENT DI STASIUN BOGOR - Yudha Citra Anugrah; Ratih Siti Aminah; Ismail Taufik Rusfien (Jurnal Penelitian Sosial Ilmu Komunikasi, 2019)
Abstract                    This study aims to determine how the public relations strategy of PT Kereta Api Indonesia (Persero) Operational Area 1 Jakarta in establishing communication to residents of the building shop tenants on the Nyi Raja Permas street in Bogor Station area before curbing occurred.                    The technique used to answer the problems presented is qualitative-descriptive using the Communication Strategy theory proposed by Effendy. This theory is used to find out about how the communication strategy carried out by Public Relations of PT. Kereta Api Indonesia (Persero) Operational Area 1 Jakarta to the residents who are disciplined. The research subjects used in this study were Suprapto as Senior Public Relations Manager, Ayep Hanapi as Junior Manager of Public Relations, Nanda Public Relations Staff and one of the residents who were disciplined. Data collection techniques using field observation techniques, in-depth interviews and documentation.                    The research results related to the communication strategy carried out by the public relations of PT Kereta Api Indonesia (Persero) Jakarta Operational Area 1, namely through two-way communication which emphasizes more on persuasive communication strategies and informative communication strategies. Persuasive communication strategies and informative communication strategies are very visible when the public relations of PT Kereta Api Indonesia (Persero) Jakarta Operational Area 1 conducted a dialogue with the tenants of the shophouse on the Nyi Raja Permas street in Bogor Station area through a socialization program, here the Public Relations of PT Kereta Api Indonesia (Persero) explained to residents that the area would later be built residential area integrated with the station and residents who would be disciplined would be moved or relocated to Pasar Kebon Kembang Bogor, of course the Public Relations of PT Kereta Api Indonesia (Persero) Daerah Operasi 1 Jakarta also explained informally that this development project was a government project to improve the efficiency of the use of rail transportation. Keywords: Communications Strategy, Land Controlling, Transit Oriented Development